The Impact of Digital Platforms on Moral Values: Investigating Opportunities and Challenges among Freshmen at UMYU Katsina - Fatima Atiku; Nasir Abba Yusuf (Scientia Publica Media, 2025)
The use of digital platforms by freshmen in the Department of Science and Vocational Education at Umaru Musa Yar’adua University (UMYU), Katsina, regarding their moral convictions is examined in this study. A survey was completed by 200 freshmen chosen using simple random technique as part of a quantitative research approach. Through the questionnaire, data was collected regarding digital platforms use, its benefits and drawbacks, and its purported impact on moral values. A reliability test of the questionnaire was conducted using 30 respondents from a different department, yielding a Cronbach’s alpha of 0.85. Descriptive statistics like mean and standard deviation were used in the data analysis. Additionally, Spearman’s rank-order correlation was used to establish the link between digital platforms use and moral values. The results demonstrate that digital platforms significantly improve students’ communication skills, social relationships, and access to educational resources. However, there are also disadvantages, such as missed time, exposure to explicit material, and addiction, which may affect students’ moral conduct. It has been discovered that there is a moderately positive correlation between moral values and digital platforms use (r = 0.401, p = 0.001), indicating that changes in moral behavior are associated with increased digital platforms use. The poll has raised issues with cyberbullying, cybercrime, health issues, and the financial consequences of digital platforms use. Despite these challenges, respondents acknowledged the potential of digital platforms to foster empathy and raise environmental awareness. Given these results, the study suggests the establishment of digital literacy initiatives, digital platforms risk awareness campaigns, and tactics to encourage the utilization of digital platforms that is balanced in order to reduce its drawbacks and maximize its benefits.